ANALYSIS OF THE IMPLEMENTATION OF THE INDONESIA MUSLIM TRAVEL INDEX (IMTI) STANDARD IN THE DEVELOPMENT OF HALAL TOURISM DESTINATIONS AT GENTONG MAS TOURISM SITE, WAJAK DISTRICT, MALANG REGENCY - Umrotus Sholikah; Septia, Vina Aula (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2024)
This research aims to analyze the implementation of the Indonesia Muslim Travel Index (IMTI) standards in developing a halal tourism destination at Gentong Mas Tourism Site, Wajak District, Malang Regency. A qualitative approach was employed using interviews and direct observations involving managers, employees, and visitors. The study focused on four main IMTI parameters: access, communication, environment, and services. The findings indicate that the implementation of halal tourism standards at Gentong Mas has covered several essential aspects, such as providing prayer facilities, halal-certified restaurants, and Islamic-based services. However, challenges remain in terms of accessibility, particularly in transportation to the site, which still requires improvement. The communication aspect also needs enhancement, especially in digital information availability and stakeholders’ understanding of halal tourism principles. In terms of environment, there has been an increase in domestic visitor arrivals and a strong commitment to developing halal tourism, although supporting facilities like Wi-Fi still need optimization. Regarding services, halal facilities are available but not yet fully compliant with IMTI standards, particularly concerning cleanliness and Islamic accommodation standards. Overall, this study concludes that Gentong Mas Tourism has significant potential to become a leading halal tourism destination in Malang Regency if it can optimize the IMTI standards through enhanced facilities, services, and Sharia-based management practices.